COMPARISON BETWEEN RELEASABLE SCLERAL BUCKLING AND VITRECTOMY IN PATIENTS WITH PHAKIC PRIMARY RHEGMATOGENOUS RETINAL DETACHMENT. Issue 1 (January 2020) - Zhao, Xiujuan; Huang, Li; Lyu, Cancan; Liu, Bingqian; Ma, Wei; Deng, Xiaoyan; Jiang, Huaiyan; Wang, Yan; Yu, Xiling; Ding, Xiaoyan; Luo, Yan; Ma, Jin; et al.
Abstract : Purpose: To compare the efficiency of releasable scleral buckling (RSB) and pars plana vitrectomy (PPV) in the treatment of phakic patients with primary rhegmatogenous retinal detachment. Methods: The current study was a prospective randomized clinical trial. One hundred and ten eyes from 110 patients with primary rhegmatogenous retinal detachment and proliferative vitreoretinopathy of Grade B or less were included in this study. The patients were randomly allocated into an RSB group and a PPV group. The functional and anatomical success was compared between groups. Results: The primary anatomical success rate (PPV 41/43 [95.35%] and RSB 38/41 [92.68%]) and final anatomical success rate (PPV and RSB 100%) showed a nonsignificant difference. The best-corrected visual acuity, intraocular pressure, and complications were not different between the groups. However, the incidence of cataract progression was higher in the PPV group (26 of 43 [60.47%]) than in the RSB group (4 of 41 [9.76%]) at the 12-month follow-up. The subfoveal choroidal thickness increased significantly in the RSB group 3 months after surgery, but no longer differed at the postoperative 6-month and 12-month follow-ups. The axial length had increased significantly 1 month after surgery, but the difference was no longer significant at 3 months, 6 months, and 12 months. Conclusion: The RSB and PPV procedures have the same effects on the functional and anatomical success for patients with phakic primary rhegmatogenous retinal detachment. Nevertheless, based on the few cases of intraocular complications and cataract progression, we believe that the RSB technique should be preferentially recommended. Abstract : By comparing releasable scleral buckling and pars plana vitrectomy in the treatment of phakic patients with primary rhegmatogenous retinal detachment, we found that releasable scleral buckling and pars plana vitrectomy procedures have the same effects on the functional and anatomical success for patients with phakic primary rhegmatogenous retinal detachment, but releasable scleral buckling was associated with fewer complications.